A phenomenological study of organizational change in an urban community college system - Rodriguez-McClellon, Leslie (Kansas State University, 2020)
The purpose of this study was to explore the lived experience of participants during the organizational change process initiated by the Houston Community College System (HCCS). A qualitative research method, specifically, a phenomenology approach, was used to evidence the lived experiences of participants during this phenomenon. Fourteen full-time administrators, faculty, and staff were selected through the purposeful and systematic sampling process. Participants must have worked for HCCS three years or more. This study investigated the initiation of organizational change, the framework selected for transformation, and the lived experiences of individuals during this process. Kotter’s eight stages of change were employed for transformation into a matrix organizational. Seven major themes and three minor themes represent the findings depicting the essence of participant experiences with the change process and matrix structure. The study’s findings indicate change being initiated with the appointment of a new chancellor and the need for centralization to increase efficiency as the reason Kotter’s change process was selected. Implementation was described as top-down but involved stakeholder input in multiple forums, multichannel communication, and transparency. Institutional size and entrenched environmental habits raised communication barriers making change difficult. Participants described experiences consistent with the change cycle model but described the change process as positive and satisfying. Participants described the matrix as producing an incomplete cultural change, making some processes more frustrating and confusing. Implications of this study found organizational change strategies, leadership characteristics and skillset, and the human need important to transformation.
Keywords: Organizational change; Organizational structure; Organizational behavior; Educational leadership; Transformational change; Matrix in higher education